2021
DOI: 10.3390/cancers13020311
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Metabolic Adaptations to the Acidic Microenvironment of Osteosarcoma Cells Unveils Sphingosine 1-Phosphate as a Valuable Therapeutic Target

Abstract: Acidity is a key player in cancer progression, modelling a microenvironment that prevents immune surveillance and enhances invasiveness, survival, and drug resistance. Here, we demonstrated in spheroids from osteosarcoma cell lines that the exposure to acidosis remarkably caused intracellular lipid droplets accumulation. Lipid accumulation was also detected in sarcoma tissues in close proximity to tumor area that express the acid-related biomarker LAMP2. Acid-induced lipid droplets-accumulation was not functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 90 publications
(132 reference statements)
2
19
0
Order By: Relevance
“…An acidic pH further drives resident or tumor-recruited MSCs to secrete pro-tumorigenic mediators [24,25]. We have extensively shown that a low pH directly influences OS cell behavior [26][27][28][29][30] and reprograms tumor-associated MSCs into an OS-supporting phenotype. Specifically, a low pH activates the NF-κB inflammatory pathway in MSCs by inducing expression of the RelA proto-oncogene NF-κB subunit (RelA), RelB proto-oncogene NF-κB subunit (RelB), and nuclear factor kappa B subunit 1 (NFKB1), as well as nuclear internalization of the NF-κB complex, which, in turn, activates the transcription of IL6 and IL8.…”
Section: Introductionmentioning
confidence: 99%
“…An acidic pH further drives resident or tumor-recruited MSCs to secrete pro-tumorigenic mediators [24,25]. We have extensively shown that a low pH directly influences OS cell behavior [26][27][28][29][30] and reprograms tumor-associated MSCs into an OS-supporting phenotype. Specifically, a low pH activates the NF-κB inflammatory pathway in MSCs by inducing expression of the RelA proto-oncogene NF-κB subunit (RelA), RelB proto-oncogene NF-κB subunit (RelB), and nuclear factor kappa B subunit 1 (NFKB1), as well as nuclear internalization of the NF-κB complex, which, in turn, activates the transcription of IL6 and IL8.…”
Section: Introductionmentioning
confidence: 99%
“…These pathways can regulate oncogenes or oncometabolites or be involved in the generation of bioactive lipids. In the former case, the RAB39A-RXRB axis has been shown to have a prominent role in the development of osteosarcoma stemness and aggressiveness at a pH of 6.5 [145], while in the latter case, the pH-dependent accumulation of S1P seems to be of paramount importance in the survival and growth potential of osteosarcoma xenografts [82].…”
Section: Targeting Acidosis In Bone Sarcomasmentioning
confidence: 99%
“…Extracellular acidosis has also been described to influence anticancer immune response and autophagy in a number of solid tumours. However, the role of autophagy in mediating survival to acidosis has not been confirmed in osteosarcoma, where the autophagic flux seems to be unchanged between pH conditions (7.4 and 6.8) [37,82], and the impact of acidosis on the infiltration of inflammatory or immune cells has not been explored thus far. Furthermore, the system by which tumour cells can sense extracellular acidosis has not been deeply investigated yet, but few specific sensors have been identified.…”
Section: Effect Of Acidosis On Sarcoma Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to reverse and prevent this damage would be to replace these acid sensitive lipids with lipids that are better suited for, or protected from, acid exposure. It has been shown previously that cells adapted to an acidic extracellular environment have increased expression of LAMP2b and increased representation on the plasma membrane [ 13 , 52 , 53 , 54 ]. Due to the acidic nature of the lysosomal lumen, the lipid composition of the inner leaflet of the lysosomal membrane has an increased concentration of lipids that are resistant to acid hydrolysis.…”
Section: Causes and Consequences Of Acid Induced Lysosomal Dysregulationmentioning
confidence: 99%